Orientation and lattice matching of CoNi nanowires embedded in SrTiO3: unveiling novel strain relaxation mechanisms in vertically aligned nanocomposites. Issue 28 (2nd July 2020) - Weng, Xiaorong; Hennes, Marcel; Tran, Thomas; Casaretto, Nicolas; Demaille, Dominique; Vidal, Franck; Zheng, Yunlin
Abstract : Unveiling complex structural rearrangements and novel strain relaxation mechanisms in vertically aligned nanocomposites. Abstract : Strain relaxation occurring during epitaxial thin film growth on lattice mismatched substrates has been studied extensively. However, it remains unclear whether existing concepts, developed to describe planar interfaces, still apply to vertically aligned nanocomposites (VANs). In these hybrid systems, which consist of nanowires (NWs) epitaxially coupled to a surrounding single crystal matrix, the structure of the vertical heterointerface is still terra incognita . In the present work, we study CoNi:SrTiO3 as a prototype VAN with large lattice mismatch between the oxide host and the embedded metallic phase. We show that the NWs display a variety of strain states: we identify NWs with huge average tensile strains (2.4 to 4.2%) along their [001] axis, as well as partially relaxed segments, with (101) and (111) planes almost parallel to those of the matrix. An additional relaxation mechanism is identified in Ni-rich VANs, where the rotation of parts of the NWs provides lattice matching for a set of (101) planes at the NW/matrix interface. Surprisingly, this tilting mechanism depends on the composition of the CoNi alloy. For high Co content (57% and 78%), the lattice matching with the matrix is along one set of (111) planes, with creation of (111) stacking faults, a behavior that can be attributed to the increasing influence of the fcc/hcp phase transition. This sheds light on the complex structural rearrangements at play in VANs and illustrates the fundamental differences between planar and vertical epitaxy in metal/oxide systems.